Balanced carrier injection of quantum dots light-emitting diodes: the case of interface barrier of bilayer ZnO electron transport layer. (1st October 2018) - Tu, Yufei; Wang, Shujie; Zhang, Yidong; Chen, Ling; Fang, Yan; Du, Zuliang
Abstract: Unbalanced carrier injection is one of the most important reasons for the efficiency roll-off in quantum dot light-emitting diodes. Reducing the electron injection can effectively balance the carrier transport and improve the optoelectronic performance of the device. In this work, a bilayer ZnO electron transport layer was fabricated by twice spin-coating and annealing methods. More than 60% of electrons are effectively blocked by the ZnO interface barrier compared with the standard device, resulting in increasing the maximum luminance of the device from 25 390 to 48 220 cd m −2 and the current efficiency from 1.5 to 3.2 cd A −1 .